Phase Equilibrium of n-Nonane plus n-Decane for Low-Temperature Thermal Energy Storage: Insights into Odd-Even Effects - Sequeira, Maria C. M.; Nikitin, Timur; Caetano, Fernando J. P.; Diogo, Herminio P.; Fareleira, Joao M. N. A.; FAUSTO, RUI (Springer, 2025)
The present article presents the solid–liquid phase diagram of a binary system composed of an n-alkane with an odd number of carbon atoms, namely, n-nonane (n-C9), with an even-numbered one, namely n-decane (n-C10). This work is part of a series of phase equilibrium studies on n-alkanes for low-temperature thermal energy storage (TES) applications. The ultimate purpose of this work is to investigate the adequacy of this binary system to be used as a Phase Change Material (PCM) at low temperatures. Additionally, along the equilibrium studies on linear alkanes, an interesting feature has emerged: the solid–liquid phase diagrams of binary n-alkane systems apparently show a striking dependence on the odd or even number of carbon atoms in their chains. The phase diagram for the system n-C9 + n-C10 has primarily been obtained using Differential Scanning Calorimetry (DSC), whose results have been complemented by Hot-Stage Microscopy (HSM) and low-temperature Raman Spectroscopy results. The DSC analysis provided both the temperature and enthalpy values for the observed solid–liquid and solid–solid phase transitions. The n-C9 + n-C10 binary system seems to display a peritectic solid–liquid phase diagram at low temperatures. The peritectic temperature found was 222.41 K, with a peritectic composition around xnonane = 0.60. Those results confirmed the initial suggestions that this would be a peritectic system, based on previously observed odd–even effects on phase equilibrium behavior of alkane mixtures. The goal of this work is to extend new insights into the solid–liquid phase equilibrium behavior of the binary system n-C9 + n-C10, a topic not yet covered in the literature. This information, consequently, provides practical and essential information on the potential use of this system as PCM for low-temperature TES applications. Additionally, it contributes to support the important discussion on the effect of odd–even number of carbons of the individual n-alkanes in the solid–liquid phase equilibrium behavior of their binary mixtures. The solid–liquid diagram of this system is being published for the first time, as far as the authors are aware. © The Author(s) 2025.
Keywords: Low-temperature thermal energy storage (TES); n-alkanes; Odd–even effects; Phase change material (PCM); Solid–liquid phase diagram